COMPARISON OF SATISFACTION AND OUTCOME OF PPIUCD AND INTERVAL IUCD AT A TERTIARY CARE CENTER IN WESTERN RAJASTHAN - Bharia, Monika; Jakhar, Rekha; Choudhary, Ankita; Vishnoi, Nirmla (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: A prospective study is to compare satisfaction and outcome of post-placental intrauterine device (PPIUCD) and interval intrauterine device (IUCD) at a tertiary care center in western Rajasthan. Methods: This is an observational study on 150 women of reproductive age group (19–45 years) who had been inserted with copper-T 380A in postpartum period and within 6 weeks of delivery between July 21 and June 22, done at department of Obstetrics and Gynaecology, Dr. S. N. Medical College, Jodhpur, Rajasthan, India. Women were categorized into Group A (postpartum IUCD) and Group B (interval IUCD). In Group A, the Cu-T-380-A was inserted intrauterine in postpartum period. In group B, CuT-380-A was inserted after 4–6 weeks of delivery by withdrawal technique. Results: The risk of other complications such as bleeding, pain in lower abdomen, and infection is relatively high in interval IUCD insertion as compared to PPIUCD insertion (p>0.05). The removal rate for bleeding and/or pain was found to be lower in PPIUCD group. Expulsion rate for group A (PPIUCD) was 6% and 2.66% in group B (p=0.257). Of total 13 removal, in group A, maximum 9 (69.23%) were removed at 6 months and 4 (30.77%) were removed at 6 weeks. Of total 16 removal, in group B, 13 (81.25%) were removed at 6 months and 3 (18.75%) were removed at 6 weeks. (0.752). Satisfaction rate for group A (PPIUCD) was 88.67% and 88% in group B. Conclusion: PPIUCD insertion is equally effective and safe method of contraception as interval IUCD insertion with lower incidence of side effects.